Fatigue and corrosion as a threat for steel heritage bridges - Macho, M. (2018)
The combined effects of corrosion and fatigue have become a topic issue in recent times. Decades-old steel bridges that are still in service need to be reassessed. However, there is no relevant background information that can be used in assessment of this phenomenon. For this reason the aim of the research presented in this paper was preparation and execution of laboratory tests on real bridge components that were deteriorated by corrosion. Experimental tests were performed to find out how corrosion weakening affects the fatigue strength of members. The evaluation of the tests indicates that the service life of members may be significantly reduced due to fatigue. The paper ends with recommendations on how the loss of material due to corrosion could be taken into account for an assessment the residual lifetime of members